Education and training: values and mediation of worlds in colonial Angola colonial - Silva, Lucia Helena Oliveira [UNESP] (Univ Federal Santa Maria, 2024)
The entry of Spiritan missionaries into Angola from the second half of the 19th century sought to support the Portuguese presence in the territories in the colonization process. However, to know and develop the process it was necessary to understand the worlds and a mediation work was developed by several religious people who studied customs and ways of living among the different autochthonous groups of Bantu formation that privileges the orality given by traditional knowledge. The school in this knowledge was not limited to a specific geographic location and the family hierarchy was respected. These values start to be challenged directly and indirectly with the presence of new customs and the process of Europeanization that allows people to adapt to the majority of other cultures. Our interest was to analyze the educational processes carried out in Catholic and Protestant missions in the context of resistance andpermanence of illegal slavery
Keywords: Angola; Education; Congregation of the HolySpirit